Preparation of Graphene-Modified Anticorrosion Coating and Study on Its Corrosion Resistance Mechanism - Peng Wang; Dayong Cai (International Journal of Photoenergy)
When aluminum alloy is present in a Cl−-rich environment, the surface oxide film is easily damaged, resulting in faster dissolution of the substrate. The application of graphene-modified anticorrosion coating can effectively prevent the occurrence of corrosion. In this study, to explore the corrosion resistance of graphene-modified anticorrosion coating on the surface of aluminum alloy, we prepared graphene-modified anticorrosion coating on the surface of aluminum alloy and investigated the corrosion resistance mechanism. Epoxy resin primer and polyurethane top coat were modified by predispersed reduced graphene oxide (rGO). Scanning electron microscope (SEM) and Raman spectrum were used to investigate the microstructure of graphene-modified anticorrosion coating, and it was found that the addition of rGO could effectively improve the porosity defect of epoxy resin primer. Electrochemical workstation was used to quickly characterize the corrosion resistance of graphene-modified anticorrosion coating, and the change of the electrochemical curve during soaking in 3.5% NaCl was investigated every 5 hours. It was found that the application of rGO to modify the anticorrosion coating could improve the corrosion resistance of the anticorrosion coating, and as the soaking time increased, the corrosion resistance of graphene-modified anticorrosion coating changed regularly. The study results indicated that when the content of rGO was 0.4%, the porosity of epoxy coating decreased from 1.54% to 0.33%, the porosity dropped by an order of magnitude, and the self-corrosion voltage was relatively positive (-0.72434 V). The self-corrosion current density was the lowest (1.948×10−6 A/cm2), and at the low frequency, the impedance modulus was the highest (103). After the equivalent circuit fitting, the dispersion index was relatively high, the dispersion effect was relatively weak, and the corrosion resistance of the coating was improved. For graphene-modified anticorrosion coating, in the early stage of corrosion protection, the existence of pores and other defects in the coating might increase the dispersion effect, resulting in greatly decreased corrosion resistance of the coating. In the middle stage of corrosion protection, the pores in the coating would be completely filled by corrosive ions, resulting in a weakened dispersion effect. Therefore, the decrease in the corrosion resistance of the coating was slowed down and became stable.